2015
DOI: 10.1038/srep09291
|View full text |Cite
|
Sign up to set email alerts
|

Cu2ZnSnS4 absorption layers with controlled phase purity

Abstract: We report the synthesis and characterization of Cu2ZnSnS4 (CZTS) with controlled phase purity. The precursor was first prepared using sequential electrodeposition of Cu, Zn, and Sn in different orders. The Cu/(Sn+Zn) ratio in each stacking order was also varied. The precursor was subjected to annealing at 200°C and sulfurization at 500°C in a 5%-H2S/Ar atmosphere for the formation of CZTS. The phase evolutions during the electrodeposition and annealing stages, and the final phase formation at the sulfurization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…The Cu 2 ZnSnS 4 (CZTS) quaternary compound is widely discussed over the last few years as an active layer in thin films photovoltaic devices1234567891011. Although the electronic properties of the CZTS-heterojunction solar cells have been studied extensively the knowledge of the CZTS basic properties is still limited.…”
mentioning
confidence: 99%
“…The Cu 2 ZnSnS 4 (CZTS) quaternary compound is widely discussed over the last few years as an active layer in thin films photovoltaic devices1234567891011. Although the electronic properties of the CZTS-heterojunction solar cells have been studied extensively the knowledge of the CZTS basic properties is still limited.…”
mentioning
confidence: 99%
“…CZTS films can be prepared by vacuum-based methods like electron beam evaporation [7], sputtering [8] etc., and non-vacuum techniques like dip coating [9,10], spin coating [11], electrodeposition [12] etc. Among the vacuum-based techniques, CZTS films can be prepared by (i) sulphurization of the metallic precursors deposited sequentially [13][14][15], (ii) deposition of metallic sulphide precursor films and annealing in an inert environment [16,17] and (iii) deposition using a quaternary CZTS target [5,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Su et al [15] fabricated CZTS films through sequential electrodeposition of metallic precursors and observed that the compositional ratio and stacking order have a major role in CZTS phase formation and they successfully prepared a 93% phase pure CZTS film with a glass/Zn/Sn/Cu precursor stack. Recent studies from Thota et al [20] and Olgar et al [21] also reveal that films having a Cu layer adjacent to both Sn and Zn layers have enhanced performance as an absorber layer due to the uniform diffusion of the precursor layers while annealing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples are Cu 2 S and SnS 2 (see, e.g., Refs. [6,[14][15]) with band gaps of 1.2-1.8 eV [15] and ~2.2 eV [16], respectively, that can be formed in CZTS at annealing temperatures T≥350 °C. Band gap of SnS is ~1.32 eV [17], so the SnSbased secondary phases might play important role in electro-optical properties of CZTS.…”
Section: Introductionmentioning
confidence: 99%